The Effect of Alium Satium Extract on the Glomerular Diameter of STZ -induced Sprague dawley Rats - Susilorini, Susilorini; Indrayani, Ulfah Dian; Soffan, Moch. (Fakultas Kedokteran; Universitas Islam Sultan Agung (UNISSULA), 2013)
Hyperglycemia exert toxic effect in kidney.The aim of this study was to investigate the short term effect of ethanolic extract of garlic in preventing nephropathy following streptozotocin (STZ) induced rats. Twenty male Sprague dawley rats were randomly divided into 4 group, all group induced induced by single dose intraperitoneal injection of 40 mg kg-1 of streptozotocin (STZ). Treatment with 3 doses ethanolic extract of garlic (0,1; 0,25; 0,5 mg kg-1 day-1) was followed for 14 days, then the left kidneys were excised and histhopathological studies were carried out using scanner 3D Hitech and Panoramic view software. Statistical analysis have been done using non parametric analysis Kruskall Wallis. The study revealed that glomerular diameter of the treatment rats was significantly different from the control group (p=0,0001). Increasing doses didn’t make difference. The ethanolic extract of garlic (Allium sativum) influences the diameter glomeruli but increasing doses has no effect on the glomerular diameter.